2013
DOI: 10.1063/1.4819771
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated pinning in a magnetic domain-wall conduit

Abstract: In spintronic devices relying on magnetic domain-wall (DW) motion, robust control over the DW position is required. We use electric-field control of perpendicular magnetic anisotropy to create a voltage-gated pinning site in a microstructured Pt/Co/AlOx DW conduit. A DW pins at the edge of a gate electrode, and the strength of pinning can be tuned linearly and reversibly with an efficiency of 0.22(1) mT/V. This result is supported by a micromagnetic model, taking full account of the anisotropy step at the gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The strength and symmetry of the magnetic anisotropy, however, are preserved upon repeated domain-wall cycling in an applied electric field. Thus, contrary to other electric-field effects [13][14][15][16][17][18][19][20][21][22][23][24][25], the mechanism discussed in this paper does not alter the magnitude of magnetic anisotropy. Instead, the magnetic domain wall in the Fe film follows the sideways motion of an anisotropy boundary that is induced by a ferroelectric a-c domain wall in the BaTiO 3 substrate, while the distinctive magnetic anisotropies on top of the a and c domains are conserved.…”
Section: B Electric-field-driven Magnetic Domain-wall Motionmentioning
confidence: 54%
See 1 more Smart Citation
“…The strength and symmetry of the magnetic anisotropy, however, are preserved upon repeated domain-wall cycling in an applied electric field. Thus, contrary to other electric-field effects [13][14][15][16][17][18][19][20][21][22][23][24][25], the mechanism discussed in this paper does not alter the magnitude of magnetic anisotropy. Instead, the magnetic domain wall in the Fe film follows the sideways motion of an anisotropy boundary that is induced by a ferroelectric a-c domain wall in the BaTiO 3 substrate, while the distinctive magnetic anisotropies on top of the a and c domains are conserved.…”
Section: B Electric-field-driven Magnetic Domain-wall Motionmentioning
confidence: 54%
“…This notion has led to various demonstrations of electric-field control over the pinning strength and velocity of magnetic domain walls via voltage-induced changes of magnetic anisotropy. Examples include the use of dielectric gates or ferroelectric films to manipulate the magnetic anisotropy via charge modulation or band shifting [13][14][15][16][17][18][19][20]. Other promising methods utilize strain coupling to piezoelectric materials [21,22] or electricfield-induced ionic diffusion [23].…”
Section: Introductionmentioning
confidence: 99%
“…Even with a decrease of an order of magnitude, the current required to drive the magnetization reversal and the consequent Joule heating would constrain the packing density of component nanostructures in memory devices, as well as waste energy 5 . There is thus much interest in reducing the energy barrier to magnetization reversal, for example by electric field 8 9 10 11 or mechanical strain 12 13 14 15 16 17 18 19 20 21 22 23 . Our approach is to use strain from piezoelectric transducers to modify the anisotropy in PMA materials and thus reduce the magnetic field needed for domain wall motion.…”
mentioning
confidence: 99%
“…Recently, it has been shown that modulating the magnetic anisotropy by an applied electric field is possible, 20,21 and thus will allow for the electric field control of DW dynamics in ultrathin metallic ferromagnets. [22][23][24][25][26][27][28] Nevertheless, the search for alternative schemes allowing fast and energy-efficient DW propagation is of great relevance in advanced spintronics research.…”
Section: Introductionmentioning
confidence: 99%